Preparation of Al–Si alloys by a rapid solidification and powder metallurgy route. (15th December 2015) - Cai, Zhiyong; Zhang, Chun; Wang, Richu; Peng, Chaoqun; Qiu, Ke; Feng, Yan
Abstract: The Al–(22–50 wt.%) Si alloys are prepared by hot pressing of gas atomized Al–Si alloy powder. The microstructures, mechanical properties, physical properties, and fracture surfaces of the alloys are characterized as a function of the Si content. All the alloys are well densified with pore-free microstructure and homogeneously dispersed Si phase that is refined in size and has smooth surface. The mechanical properties of the alloys are improved gradually with increasing Si content, especially the bending strength. However, both the coefficient of thermal expansion (CTE) and thermal conductivity of the alloy decrease at the same time. The average CTE and thermal conductivity of the Al–Si alloys are 18.7–11.3 10 −6 /K and 184–145 W/m K, respectively, indicating excellent performance of these alloys. Theoretical models are used to predict the CTE and thermal conductivity of the alloys. Moreover, the thermal boundary resistance at the interface of Al and Si is also calculated. Graphical abstract: Highlights: Al–Si alloys are prepared by hot pressing of gas atomized alloy powder. The Si phase has smooth surface refined and homogeneously dispersed in the matrix. Thermal boundary resistance at the interface of Al and Si is 3.4 × 10 − 9  m 2  K/W.